2013
DOI: 10.1179/1743676112y.0000000060
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis ofβ-SiAlON whiskers: dependence of uniform morphology upon preparation conditions

Abstract: b-SiAlON whiskers with uniform morphology were prepared using reaction sintering method under different conditions. The effect of preparing conditions on the morphology of b-SiAlON whiskers was systematically studied by SEM, XRD, TEM and HRTEM. The results showed that single crystalline b-SiAlON whiskers with uniform morphology were successfully fabricated at 1773 K for 6 h under flowing nitrogen atmosphere. The well synthesised whiskers were of several hundreds of nanometres in diameter and a few hundreds of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Ji et al [17] reported that the pea-like grain could be regarded as the precursor grains of SiAlON whiskers. It was interesting to obtain the formation mechanism of β-SiAlON, which prefers a documented vapour-liquid-solid (VLS) (Figure 5) mechanism of β-SiAlON formation from a previous reported research [20][21][22]. The process of producing β-SiAlON was as follows: (1) forming the Si-Al-P liquid, including Si, Al, impurity like Fe at lower temperatures; (2) the dissolution of gas, such as…”
Section: Microstructure and Morphology Of Different Samples From Zirc...mentioning
confidence: 99%
“…Ji et al [17] reported that the pea-like grain could be regarded as the precursor grains of SiAlON whiskers. It was interesting to obtain the formation mechanism of β-SiAlON, which prefers a documented vapour-liquid-solid (VLS) (Figure 5) mechanism of β-SiAlON formation from a previous reported research [20][21][22]. The process of producing β-SiAlON was as follows: (1) forming the Si-Al-P liquid, including Si, Al, impurity like Fe at lower temperatures; (2) the dissolution of gas, such as…”
Section: Microstructure and Morphology Of Different Samples From Zirc...mentioning
confidence: 99%
“…It has been demonstrated that one‐dimensional materials, such as nanowires, whiskers, and fibers, exhibit unique structures and properties, which are exploited to build up nano‐scale reinforcements 26‐29 . Significant efforts have been devoted for in situ synthesizing one‐dimensional Sialon materials inside ceramic matrix materials 30‐32 . In these researches, one‐dimensional Sialon materials were synthesized successfully inside matrix; however, there still exists some problems that need to be further explored and discussed.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29] Significant efforts have been devoted for in situ synthesizing one-dimensional Sialon materials inside ceramic matrix materials. [30][31][32] In these researches,…”
mentioning
confidence: 99%